Measuring the Teacher's Sense of Efficacy Scale for Teachers of Children with Special Needs in Indonesia - Rachmahana, Ratna Syifa'a; Muhammad Chirzin; Khoiruddin Bashori; Halim Purnomo (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
This research aims to test the validity and analysis of the Teacher's Sense of Efficacy Scale (short form) measurement tool for teachers of children with special needs in Indonesia. In this study, researchers tested three dimensions developed by Tschannen-Moran and Hoy (2001) for measuring teaching efficacy: Efficacy in Classroom Management, Efficacy in Student Engagement, and Efficacy in Instructional Strategies, with 12 items. The research subjects were 301 teachers of children with special needs. Among the subjects are 225 female and 76 male teachers, with a median age of 26-35. The sampling method utilised in this study is purposive sampling. The data analysis method used in this research is confirmatory factor analysis (CFA). The analysis results show a GFI value of 0.9 97; CFI 0.930; TLI 0.907; RNI 0.930; SRMR 0.044; and RMSEA 0.082. Further, Rasch analysis found that all 12 items of the scale were valid and used in the study. This model allows stakeholders to gain more insights into teachers’ self-efficacy, especially regarding children with special needs.